Educational Issues of Children of the Tiwa Community of Assam A Statistical Interpretation - Dey, Tulika; Deka, Manab (JOURNAL OF INDIAN EDUCATION, 2012)
Tiwa community is one of the prominent tribes and a major ethnic group of Assam. Independent India has been paying due attention to the problems of the Scheduled Tribes and attempts are being made to deal effectively with their problems. In spite of all kinds of steps taken by the government for providing educational facilities, the Tiwa community is far below national literacy average as far as education is concerned. Our objective is to study the causes of the problems faced by the students of the Tiwa community in terms of likings, facilities, enrollment and retention. More specifically, an attempt has been made to identify causes of students’ disliking for going to school, which in turn may be useful for reducing students’ drop-outs. The study was undertaken in two districts of Assam namely Morigaon and Nagaon, where the density of population of the Tiwas is the highest. Altogether, eight villages were considered wherefrom 148 students were interviewed during data collection. Some bivariate analyses were done for a few characteristics, whereas multivariate analysis has been done using logistic regression analysis with liking for going to school by the students as the dependent variable. The analysis indicates that characteristics like gender, mid-day meal, cleanliness of school, reward by teacher and students’ liking of the teachers have significant effect on the liking of students for going to school, whereas, attributes like education of parents, mode of transportation, play material and toilets in school do not appear to have any significant effect.